Spotted fever group rickettsiae canine serosurveillance near the US–Mexico border in California. (26th November 2019) - Estrada, Irais; Balagot, Caroline; Fierro, Marian; Kriner, Paula; Iniguez‐Stevens, Esmeralda; Kjemtrup, Anne; Foley, Janet
Abstract: Background: Dogs are vulnerable to pathogens transmitted by brown dog ticks . An epidemic of Rocky Mountain spotted fever (RMSF) is underway in Mexicali, a Mexican city bordering California affecting people and dogs; several human cases have been reported in California residents who travelled to Mexico. To evaluate risks of RMSF, we conducted seroprevalence surveys in Imperial County in 2016 and 2017 using dogs as sentinels. Methods: Blood was collected from 752 dogs and was tested for antibodies against R. rickettsii, E. canis and A. phagocytophilum (as a proxy for A. platys ). Samples were considered seropositive to spotted fever group rickettsia (SFGR) if the R. rickettsia titre was ≥1:64 and seropositive to E. canis and A. phagocytophilum if the titre was ≥1:32. Owners provided information on dog age, exposure risks, health status and tick prevention. We assessed associations between SFGR seropositivity and driving distance to the nearest US–Mexico border crossing station, whether proximity to a border crossing increased likelihood of taking dogs across the border, and whether distance to the border was associated with seropositivity. Logistic regression was performed to assess relationships between the titre classes and other predictor variables. Results: 12.2% of dogs were seropositive against SFGR. Dogs close to the border were significantly more likely to be taken across the border and to be seropositive. Risk factors that increased seropositivity included owners seeing ticks on the dog (OR = 1.9), being an adult dog, travel to Mexico (OR = 3.0) and living in a rural area (OR = 4.0). There was statistically significant co‐exposure to SFGR and Anaplasma spp. Conclusion: Surveillance for brown dog tick‐vectored pathogens can help identify dogs and people at risk for RMSF. Tick prevention, particularly in dogs, and surveillance of tick‐borne pathogens can help prevent the spread of rickettsioses and other diseases in this dynamic border region.